Promoting the Right to Education through A Card: A Paradox of Indonesia's Educational Policy? - Ulum, Muhammad Bahrul; Wildana, Dina Tsalist (JILS (Journal of Indonesian Legal Studies), 2019)
In 2015, the Indonesian government unveiled the Smart Indonesia Program, or Program Indonesia Pintar (PIP). The program consisted of educational subsidies through cash transfers exclusively granted to students aged from 6 to 21 years old from poor families. This paper examines the role of the PIP subsidy pertaining to the fulfilment of the right to education. As a consequence, it resulted in a competing account between cash transfers and the minimum standard of government duties to fulfil the need for adequate educational support. There is a paradox in the government's educational policy on the fulfilment of human rights to education in dealing with the PIP program. While educational complexities faced in remote areas cannot be hindered and it is granted not solely to students from vulnerable families. Such discrepancies in programs circumstantially affirm that the government ignores the root of Indonesia's educational problems, including providing free education as its obligation to human rights. The research conducted concludes by suggesting the government to evaluate the current policies by considering budget priorities and the efficiency of providing inclusive education.